Androgyne Myth Reception in Surrealist Photography - Shik, Ida A. (Actual Problems of Theory and History of Art, 2015)
The paper explores the key strategies of the androgyne myth reception in the surrealist photography. One of the most common images of an androgyne in the surrealist photography is a phallic woman, allocated with a penis symbolically, or literally, or associated with it (works of Man Ray, Brassai, H. Bellmer, P. Molinier). This interpretation goes back to infantile fantasies about the phallic mother and has its historical parallels with images of ancient androgynous gods (according to S. Freud). The image of an androgyne as a desired unity of male and female bodies is created by H. Bellmer, whose photographs of dolls with two pairs of legs remind us that Eros is inseparable from Thanatos, an act of love is inseparable from an act of mutual destruction. The idea of an androgyne as an ideal “third sex” reflecting the initial bisexuality of human nature is represented in self-portraits of C. Cahun and P. Molinier. While C. Cahun deconstructs the concept of a sex radically, reducing it to a theatrical masquerade, P. Molinier presents the image of an androgyne as a wizard — the shaman. The author concludes that the strategies of the androgyne myth reception represented by the surrealist photography and the associated problems, such as fetishism, gender identification, intersexual dressing up, etc., still remain valid for modern culture. (works of J.-P. Witkin, C. Sherman, Y. Morimura, M. Barney).
Keywords: surrealist photography; androgyny; androgyne; modern art